Histórico, cálculo e irracionalidade de pi-grego - Oliveira, Francisco Lucas Santos (2015)
pi is a number of singular nature because several men in different historical moments lingered themselves to calculate and study it. Circles can be seen in almost all places, and as a consequence, so can pi. Due to being so present in the reality, a huge number of mathematicians devoted themselves to the study of this number and its numerical value. This work, result of much research, will show many of the different ways that the mathematicians took to find an approximation for pi. We will also approach in this work the curious founds involving this number, the famous problems around it as well as the diverse methods which were used to calculate it. The search for the numerical value took the mathematicians to assume its irrationality which was proved afterwards and will be done here. We will finish approaching how we can calculate pi in the classroom in a different way.